Anatomical Landmark-guided Strategy for Computer-assisted Reconstruction of Infrastructure Maxillary Defects Using Free Fibula Flap - Songying Wu, BDS; Jingya Jane Pu, BDS, MDS; Edmond Ho Nang Pow, BDS, MDS, PhD; Pui Hang Leung, BSc; Xing-Na Yu, BDS, MDS; Yu-Xiong Su, MD, PhD; Wei-Fa Yang, BDS, MDS, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Computer-assisted surgery in head and neck reconstruction yields predictable and favorable clinical outcomes. However, there is a lack in the optimal arrangement of the fibula bone segments to re-establish the function and aesthetics of the maxilla. Methods:. This study proposed a novel anatomical landmark-guided strategy for the virtual surgical planning (VSP) of infrastructure maxilla reconstruction using a free fibula flap. The optimal positioning of fibula segments was validated with a retrospective clinical study. Patients who underwent computer-assisted infrastructure maxillectomy and reconstruction with a free fibula flap from May 2017 to April 2024 were reviewed. Reproducibility of the landmarks and associated clinical parameters was assessed in VSP compared with the preoperative maxilla. Additionally, a structured quantitative approach was adopted for postoperative surgical outcome analysis by comparison of the postoperative maxilla and the VSP. Results:. Twenty patients fulfilled the criteria of this study. In 11 cases, we conformed to the proposed reconstruction strategy (group A). In 9 cases, we adopted a modified approach (group B) with deviations in the count of fibula segments and positioning strategy. In group A, the pooled median landmark error was 2.19 mm (interquartile range, 1.63–2.91 mm) in the VSP compared with the preoperative maxilla; in group B, the error was 4.54 mm (interquartile range, 2.05–6.15 mm). The clinical parameters demonstrated satisfactory recapture of the alveolar arch and maxillary width. Conclusions:. This anatomical landmark-guided strategy was validated with satisfactory reproducibility of the quantitative metrics in the VSP. The anatomical landmarks and associated clinical parameters provided a structured quantitative approach for postoperative analysis of computer-assisted maxillary reconstruction using FFFs.